Considerations on Artifacts of Digital Culture in English Language Teaching - Peter Schildhauer; David Gerlach; Kristin Weiser-Zurmühlen (Wissenschaftliche Einrichtung Oberstufen-Kolleg der Universität Bielefeld, 2023)
In this contribution, we present some considerations on the role digital artifacts could and should play in 21st-century language teaching. Our argument focuses on social media feeds (in particular: the Instagram feed) as a prototypical example of digital artifacts. We highlight the potentially manipulative force of the Instagram feed using the example of conspiracy theories as a case-in-point. Illustrating our argument with examples from ongoing empirical work, we suggest and elaborate on three challenges entailed by implementing social media feeds in the language classroom: They constitute a moving target due to their dynamics, inspire a false sense of security because of filter bubble as well as third-person effects and confront us with the question of "What can we do in the classroom?". We conclude by suggesting possible components of Critical Digital Literacy as an answer to this question.